Altura de corte na composição nutricional da forragem e nos nutrientes minerais da fração não colhida de milho para silagem - Bertapelli, Marcelo (2014)
The effect of four cutting heights were evaluated (15, 25, 35 and 50 cm) on the corn silage quality and the potential of nutrients restitution to the soil obtained from corn crop residues. The corn hybrid used was Dekalb 789. The plants were harvested, at the point of silage, according to the predetermined cutting height. Sixteen experimental silos of PVC were utilized with 20 cm of diameter and 40 cm of height, including four repetitions for each treatment. On the residues in each cutting height were determined the contents of DM, MM, OM and macronutrients (N, P, K, S, Ca and Mg) and micronutrients (Zn, Cu, Fe and Mn). The production of milk per ton of forage and per hectare was estimated using the model Milk2006. The productivity of biomass was 12.2 t of DM/ha. The participation of different corn components on total ensiled biomass total (DM) was 39.47% of corn cobs, 34.42% of corn stalk, 24.22% of leaves and 1.89% of panicles . The height of harvest increasing from 15 cm to 50 cm reduced 10.6% DM productivity and increased the CP levels (7.88% to 9.00% DM), EE (1.84% to 2.33% DM) and FDA (31.75% to 28.00%DM).The forage feed efficiency improved, increasing the levels of TDN (65.50 to 68.23) and of ELl (1.21 to 1.27), however there was a reduction on the estimated yield of milk/ha (11.887 to 10.740 liters). The highest cutting heights evaluated 50 cm to N, S, Ca, and Mg, and 35cm to P and K, (related to the soil level) promoted the restitution to the soil of 24.9% of K, 17% of Ca, 16% of Mg, 9% of N and 5.6% of P of the total extracted from each mineral nutrient. On the same way the potential return of micronutrients extracted by the corn crops were 13% of Cu, 6% of Zn and 30% of Mn. The increase on the corn cutting height enabled, through the residues, a significant increase on the restitution of macronutrients to the production system. However for the experiment conditions, resulted on milk productivity reduction.